Punctate porokeratosis palmaris et plantaris - Padmavathy Lanka; Lakshmana Rao Lanka; Dhanalakshmi Manivachagam (Wolters Kluwer Medknow Publications, 2015)
Porokeratosis, a keratinization disorder, is probably a group of unrelated conditions with same distinctive histological appearance, featuring cornoid lamellae. A case of punctate porkeratosis in a 24 year old male patient is reported for its rarity.